UTILIZATION OF ARTIFICIAL INTELLIGENCE IN TOURISM MARKETING MANAGEMENT OF PALEMBANG CITY TO ENHANCE DESTINATION COMPETITIVENESS - Sri Wahyuni; Yuyun Yuniarsih; Anggita Rismayanti; Fikry Fathurrahman (PT. Altin Riset Publishing, 2025)
This study examines the utilization of Artificial Intelligence (AI) in tourism marketing management to enhance the competitiveness of Palembang City as a tourist destination. The main issue addressed is the lack of innovation in marketing strategies, which have not been adaptive to technological advancements. The objective of this research is to identify how AI implementation can optimize destination promotion and attract more tourists. The research was conducted in Palembang City using a qualitative descriptive method. Data collection techniques included interviews, observations, and document analysis involving tourism stakeholders. The results of the study indicate that the use of AI-based tools such as chatbots, virtual tours, and data analytics can improve marketing effectiveness and tourist engagement. The conclusion emphasizes the importance of integrating AI strategies into tourism marketing to create more personalized, efficient, and engaging promotional efforts.